Development of nutrient-rich complementary foods using locally sourced ingredients for low-income households in Eastern Ethiopia - Shewa, Anbesse Girma; Anamoo, Shewangizawe Teketele; Abera, Solomon; Ali, Mikiyas Kebede; Gelan, Jalene (Frontiers in Nutrition, 2025)
BackgroundThe prevalence of malnutrition among infants continues to be a significant issue in Ethiopia. Although commercial complementary foods are accessible in the market, their prohibitive costs render them unaffordable for low-income households. Consequently, this study was undertaken to formulate complementary foods utilizing locally available, nutrient-rich ingredients tailored for low-income households.MethodThe effect of various processing techniques—such as boiling, germination, and roasting—on the physicochemical properties of maize and groundnut flours, including proximate composition, mineral content, phytochemicals, and β-carotene levels, was evaluated using standard methodologies. A complementary food product was developed by varying the blending ratios of maize flour, groundnuts, spinach leaves, and sweet potatoes. Subsequently, the physicochemical and sensory characteristics of the product were assessed.ResultsThe processes of germination and roasting (applied to maize and groundnut) demonstrated minimal impact on the proximate composition, mineral content, and β-carotene levels while also decreasing the amounts of specific phytochemicals (such as tannins, phenols, and phytic acid) found in the raw materials. Consequently, these processed ingredients were used to formulate eight complementary food products. The results of the proximate composition analysis for the eight developed food formulas indicated that the protein content ranged from 15.35 to 16.39%. Additionally, the fat, carbohydrate, and energy values were observed to range from 8.1 to 11.9%, 59.12 to 63.07%, and 383.82 to 412.87 kcal, respectively, indicating a nutritional profile consistent with locally available commercial complementary foods. Similarly, the levels of calcium, zinc, iron, magnesium, and β-carotene were measured to range from 66.75 mg to 102.48 mg, 1.33 mg to 2.48 mg, 6.64 mg to 10.36 mg, 122.60 mg to 181.73 mg, and 113.40 mg to 197.53 mg per 100 g, respectively, alongside notably low levels of anti-nutritional factors.ConclusionIncluding supplementary food is crucial when breastfeeding alone does not adequately meet an infant’s nutritional requirements. As a result, the complementary food developed can provide 5 to 50% of the daily recommended nutrient allowance for infants.